PENGARUH SUBTITUSI TEPUNG AMPAS TAHU DAN TERIGU PADA KERUPUK TERHADAP KUALITAS HEDONIK DAN KANDUNGAN GIZI: The Effect of Substituting Tofu Dregs and Wheat Flour in Crackers on Hedonic Quality and Nutritional Content - Inang Ariawan; Bagus Setyawan; Rosiana Ulfa (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2024)
Crackers are a popular and popular food among people. Tofu dregs are often considered waste with low economic value and are easily damaged. In fact, tofu dregs have quite a high protein content. This research aims to determine the protein content in tofu dregs flour crackers and the results of hedonic tests on these products. The four treatments tested were: (K) control 100% wheat flour, (P1) 40% tofu dregs flour, (P2) 50% tofu dregs flour, (P3) 60% tofu dregs flour. The hedonic test results show gacor777 that for the parameters of crispness, color and taste, P2 is most preferred with average values ​​of 5,81% and 5.68% respectively. In terms of aroma parameters, control is preferred with an average value of 5,48%. In terms of shape parameters, P3 is preferred with an average value of 5,21%. For taste parameters, P2 was preferred with an average value of 5,65%, although control was also preferred with an average of 5,8%. The chemichal test results showed the highest protein content in P3 with an average of 17,10%, while the control had the lowest with 5.84%. The highest moinsture content was in the control with an average of 4,74%, and the lowest was in P3 with 4,5%. The overall assessment showed that crackers with 50% tofu dregs substitution (P2) were most preferred.